Integration Of Environmental Education (Green Moral) Through The Learning Of Islamic Religion Education In School - Marwiji, Muh. Hasan; Wahyudin, Wahyudin; Setiono, Joko; Ruswandi, Uus (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The environment should be a support for the continuity of human life damaged due to exploitation by humans to meet their needs. The environment is treated well with full collective responsibility involving every individual and society. Realizing the importance of this, deep world of education is known green education, green school, and eco-green which an effort is to form a generation of environmental conservationists, extinct and maintained in a sustainable manner for future generations. This study aims to obtain valid and complete information regarding the integration of environmental education with PAI learning in schools. The method used is a qualitative method by applying literature study. The results of the study state that Islamic religious education can be integrated with environmental education which leads to green morals, namely building a positive relationship between all school members and the natural environment based on values. Ecological value education through religion needs to be considered by environmentalists. In solving environmental problems not only on materialists (hardware), and software, namely through religion is also needed, planting values to form culture green is often overlooked. Education Integration Green moral through PAI learning can be done in intra curricular, extracurricular, and non-curricular activities.